WOX11-OsPRX130 module confers rice drought tolerance by maintaining ROS homeostasis in rice root - Mingfang Tan; Yijie Wang; Yu Zhao (Rice)
Abstract Plants have evolved sophisticated mechanisms to cope with drought stress. A resilient root system, coupled with appropriate levels of reactive oxygen species (ROS), is crucial for optimal growth and increased yield under drought stress. Accumulating studies have shown a strong link between root development, ROS, and drought tolerance. WOX11, as a master regulator of crown root (CR) development in rice, also governs root redox metabolism. However, it remains unknown whether WOX11 modulates ROS homeostasis in roots to facilitate adaptation to drought stress. In this study, we found that WOX11 directly binds to the promoter of the peroxidase gene OsPRX130, thereby enhancing drought tolerance by regulating CR growth. Notably, OsPRX130 is predominantly expressed in rice roots and its expression is induced by drought stress. Knockout of OsPRX130 inhibited CR growth by reducing ROS levels, ultimately compromising the drought tolerance in rice. Taken together, our findings shed light on the mechanism by which WOX11 mediates ROS accumulation through modulating the class III peroxidase gene OsPRX130 during rice CR development. This provides new insights into the functions of PRX genes during CR development. More importantly, our results deepen our understanding of how WOX11 regulates root development to enhance drought tolerance in rice and provide an alternative breeding strategy using WOX11 to control root system architecture for developing crop varieties with high drought adaptability.